A SURVEY OF WATER QUALITY IN THE ZAYANDEH ROOD RIVER - M. Assadi; P. Samar; F. Moghadam; M. Hakimipour; R. Razmi (Tehran University of Medical Sciences, 1976)
The quality of the river water is assessed in different months in different stations to evaluate the change in the quality in re1ation with the various point sources along the river. Thirteen parameters were measured in the samples manually taken from three meters off shore in 20 cm. depth in four points representing the quality in four reaches under consideration. The results revealed that natural flow of river is not adequate for a proper dilution. A minimum dissolve oxygen saturation of 19% corresponding to a DO concentration of 1.62 mg/1 was observed. A most probable number of coliform bacteria of 35000 were noticed representing a heavy bacterial pollution. Considering the percent situation water quality of the river might deteriorate in future and might not meet the prospective domestic and industrial demands.